Evaluating the Effects of Multiscale Heterogeneous Sediments on Solute Mixing and Effective Dispersion. Issue 9 (21st September 2022) - Ren, Wanli; Ershadnia, Reza; Wallace, Corey D.; LaBolle, Eric M.; Dai, Zhenxue; de Barros, Felipe P. J.; Soltanian, Mohamad R.
Abstract: The heterogeneity of sedimentary aquifers can be characterized by parameters related to the underlying sedimentary structure such as physical attributes of sediments (e.g., volume proportions and lengths of facies types). These parameters often reflect multiscale variability typically observed in the hydraulic conductivity field and the resulting fluid velocity. Although there have been many studies of solute transport processes (e.g., dispersion, mixing, and dilution) in heterogeneous media, there is still a lack of understanding of the controlling influence of sedimentary architecture on the time‐evolution of the solute plume's spreading and mixing behavior and their uncertainty. In this work, we used high‐resolution and three‐dimensional numerical simulations to investigate the time‐evolution of the effective dispersion and mixing behavior of the solute through a heterogeneous aquifer that displays multiscale sedimentary architecture. Transport simulations are performed by using the random walk particle tracking method. Our numerical experiments allow us to understand which scale of sedimentary architecture is most relevant to explaining effective dispersion and mixing. We further analyze whether or not the uncertainty in solute spreading and mixing are equally affected by the different spatial organization of sedimentary facies types. We also perform an extensive parametric study to better understand the effect of physical sediment attributes and univariate statistics of hydraulic conductivity (e.g., mean and variance) at the facies scale on both effective dispersion and mixing. Our results indicate that meter‐scale heterogeneity plays a major role in controlling solute transport processes. Moreover, the effective dispersion is more sensitive to the spatial organization of sedimentary facies type. Key Points: Geometry of larger‐scale facies types is most relevant to explain effective dispersion and mixing processes The effect of sediment properties and univariate statistics of K on mixing and effective dispersion and their uncertainty are evaluated Dispersion process is more realization dependent than mixing process